THE FRAMEWORK OF TEACHING LEARNING PROCESS OF INDONESIAN NATIONAL QUALIFICATION IN PRIVATE COLLEGE - Chontina Siahaan; Hendry Sinuraya; Donal Adrian (Sociae Polites, 2018)
The Indonesian national qualification the education system is still relatively new, Universitas Kristen Indonesia but as educators, were required to be able to exercise a marksman in conveying the, learning attractive easy to understand and give the opportunity for message receiver to express his response to a clarification on a subject discussed. A research paradigm is constructive. The kind of research is qualitative. The result showed that strategy lecturers in conveying a message or material college-based Indonesia national qualifications framework in Universitas Kristen Indonesia do with how to explain back material that has delivered, use simple sentences and give a case that up to date.